SENTIMEN ANALISIS PENGGUNA TWITTER TERHADAP SEA GAMES 2023 DENGAN METODE NAIVE BAYES - Gumilang, Wahyu; Riyandi, Albert (LP2M Universitas Nurdin Hamzah, 2023)
The development of computers and telecommunications has made people often express their opinions through social media Twitter. As recently, after the 2023 SEA Games were held in Cambodia, various kinds of tweets appeared from various sports. From this opinion, it can be seen that the country's success in holding the Sea Games by conducting a sentiment analysis. So this research was conducted to find out how the public opinion regarding the holding of the 2023 SEA Games using the Naive Bayes Classifier algorithm. The data used was 1888 data obtained by crawling Twitter data using the keywords SEA Games and RapidMiner tools. The division of training data and testing data is carried out into two comparisons, namely 50:50 and 60:40. The best accuracy results are obtained with a data comparison of 50:50, which is 70.15%, while a data comparison of 60:40 has a smaller result, namely 70.07%.